2018
DOI: 10.1002/ejoc.201701690
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Syn Addition of 1,3‐Diones to Internal Ynamides Catalyzed by Zinc Iodide

Abstract: 1,3‐Diones are already established as nucleophiles to perform additions to ynamides; the highly selective hydroalkoxylation of internal ynamides is now described. Several catalytic systems have been compared to perform this transformation, including transition‐metal‐based catalysts and Lewis acids. ZnI2 was found to be both very active and highly selective providing only E adducts through a syn addition. Investigation of the scope and limitations showed that this catalyst was compatible with various functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…13 C NMR (151 MHz, CDCl 3 ): δ = 149.9, 146.0, 135.4, 128.8, 128.8, 128.3, 128.2, 127.9, 124.3, 47.4 ppm. Spectral data are consistent with those in the literature . MS (APCI, m/z ): calcd.…”
Section: Methodssupporting
confidence: 86%
“…13 C NMR (151 MHz, CDCl 3 ): δ = 149.9, 146.0, 135.4, 128.8, 128.8, 128.3, 128.2, 127.9, 124.3, 47.4 ppm. Spectral data are consistent with those in the literature . MS (APCI, m/z ): calcd.…”
Section: Methodssupporting
confidence: 86%
“…Later, the same group showed that when the Lewis acid ZnI 2 was employed as the catalyst, hydroalkoxylation of internal ynamides with 1,3-diones could occur readily at room temperature and α-alkoxy enamides were afforded with high yields and selectivities (Scheme 39). 85 Aryl and alkyl-substituted ynamides were well tolerated in the process. Oxacyclic 1,3-dione was a suitable coupling partner as well.…”
Section: C-o Bond Formationmentioning
confidence: 99%
“…ZnI 2 catalyzed intermolecular hydroalkoxylation of ynamides 6 with 1,3-diketones 7 was reported by Clavier and co-workers for the stereoselective synthesis of enol ethers 8 (Scheme 6). [14] The developed method offered access to various synthetically useful enol ethers in excellent yield and diastereoselectivity. The TIPS-alkynes (R 2 =TIPS, triisopropylsilyl) gave a trace amount Chemistry-A European Journal the major product along with aliphatic ketone as the minor product.…”
Section: Transition Metal-catalyzed Intermolecular Hydroalkoxylation: Synthesis Of Enol Ethersmentioning
confidence: 99%